Rangeliosis: histopathological analysis, hematology and molecular detection of canine Rangelia vitalii in Rio Grande do Sul, Brazil - Gabriela Fredo (Ciência Rural, 2017)
In the period from January 2004 to December 2015, 56 dogs were diagnosed with rangeliosis in the Setor de Patologia Veterinária at Universidade Federal do Rio Grande do Sul (SPV-UFRGS). The main hematological abnormalities were thrombocytopenia and anemia. The affected dogs showed signs of apathy, anorexia, fetid and bloody diarrhea, vomiting, and dehydration. At necropsy, the main changes were jaundice, splenomegaly, hepatomegaly, and lymphadenomegaly. Histological analyses revealed parasitophorous vacuoles of Rangelia vitalii in cytoplasmic endothelial cells, mainly in the heart, kidneys, lymph nodes, intestines, and pancreas. Inflammation characterized by mononuclear cells was predominant in the analysis, and most was due to the presence of plasma cells. Other lesion types observed were lymphoid hyperplasia, extramedullary hematopoiesis, erythrophagocytosis, and erythroid lineage hyperplasia in bone marrow. Of the total number of animals, 49 were diagnosed using necropsy and histological analysis, and seven were diagnosed using a molecular analysis (i.e., PCR and genetic sequencing of blood samples). This paper presented a different method of diagnosing rangeliosis in canines. This approach involved histological methods including the quantification and determination of the intensity and distribution of the infectious agent in different organs.